PEMBERDAYAAN KELOMPOK TANI DALAM PEMBUATAN PHOTOSYNTHETIC BACTERIA (PsB) DAN BIOSLURRY UNTUK MENDUKUNG PERTANIAN BERKELANJUTAN DI DESA MEDOWO KABUPATEN KEDIRI - Suprianto, Agung; Sumarmi, Sumarmi; Ririh Windayu, Cinde; Arinta, Dicky (Jurnal Abdimas Bina Bangsa, 2024)
Medowo Village in Kediri Regency has great potential in the agriculture and livestock sector, but still relies on expensive and hard-to-obtain chemical fertilizers. Additionally, the suboptimal management of livestock waste causes environmental pollution. This service program aims to empower farmers in Medowo Village through training in the production of organic fertilizer using Photosynthetic Bacteria (PsB) and bioslurry. The service methods include socialization, training, and mentoring the "Tani Makmur" farmer group to understand and independently apply the techniques for producing organic fertilizer. This community service activity can reduce farmers' dependence on chemical fertilizers while optimizing the use of livestock waste as an environmentally friendly source of plant nutrients. The evaluation results show an increase in farmers' understanding and skills in producing and applying organic fertilizers. Thus, this program has the potential to support sustainable agriculture in Medowo Village and can serve as a model for the implementation of environmentally friendly farming practices in other regions.